Sustainable agricultural reform and the persistence of poverty in Indonesia: A path dependence analysis. Issue 1 (April 2021) - Karim, M F; Mursitama, T N; Affandi, R A; Permana, A; Kholid, M
Abstract: The most important characteristic of poverty in Indonesia is the prevalence of poverty in the agricultural sector. What is the main root of poverty in the agricultural sector in Indonesia? By analyzing the historical account of agrarian reform, the paper examined the evolution of policy toward peasant and agricultural sector in Indonesia from 1960s. It argued that the lack of peasants' accessibility of land ownership, government reluctance to revitalize agricultural sector, as well as the failed land reform agenda have contributed toward massive poverty in Indonesian agricultural sector. The paper provided further analysis of current Indonesian policy toward agricultural sector.